Topic "Fox Optics" in Higher Educational Institutions Teaching Through the Method of “Working in Small Groups” - Seytimbetova Gulbadan Azatovna (International Journal on Orange Technologies, 2020)
The use of modern teaching methods leads to high efficiency in the teaching process. When choosing teaching methods, it is advisable to choose based on the didactic function of each lesson. While maintaining the traditional form of the lesson, enriching it with methods that activate the activities of various learners leads to an increase in the level of mastery of learners. To do this, high efficiency can be achieved through the rational organization of training, the interest of learners by the educator, the choice of methods and tools in accordance with the content of the studied material. The level of mastery, practical skills and competencies of learners can be developed through interactive or interactive teaching methods.